Are we underestimating the impact of COVID-19 on children's physical activity in Europe?—a study of 24 302 children. (12th January 2022) - Kovacs, Viktoria A; Brandes, Mirko; Suesse, Thomas; Blagus, Rok; Whiting, Stephen; Wickramasinghe, Kremlin; Okely, Anthony D
Abstract: This repeat cross-sectional study investigated the impact of lockdown in Europe in Winter (January and February 2021) on children's and adolescent's physical activity (PA) and recreational screen time (RST), and compared PA to the lockdown in Spring 2020. An online survey was administered ( n  = 24 302; 6–18 years; 51.7% boys) in nine countries. PA and RST were assessed by 7-day recall. In total, 9.3% of children (95% confidence interval: 6.9–11.7) met WHO PA recommendation, which was half of the proportion observed in Spring 2020 [19.0% (18.2–19.9)]. Sixty percent exceeded the RST recommendations. This suggests that winter lockdown could have a more negative impact on PA than in spring.